(untitled) (Research, Society and Development, 2022)
Maxillofacial prostheses are among the modalities of prosthetic rehabilitation but the disinfectant solutions for their cleaning have been barely explored. The purpose of the present study was to evaluate the antibacterial effects of a Brazilian green propolis glycolic (PGL) solution on the removal of biofilm from the surface of two maxillofacial elastomers (room temperature vulcanization [RTV] and high consistency silicone rubber [HCR]). A total of 42 specimens (3×10 mm) were made with these two elastomers and Staphylococcus aureus was allowed to grow for 24 hours on the surface of the biomaterials. Specimens (n=3) were randomly allocated to the following treatment groups by immersion for 15 minutes: 0.9% saline solution; 2% chlorhexidine gluconate (CHX); 11%, 16% and 20% PGL; and Daro Brand® antimicrobial liquid agent and antibacterial gel soap. Quantitative assessment was performed by counting the number of colony-forming units (CFU). Two-way ANOVA was employed for data analysis. Specimens of both maxillofacial elastomers treated with PGL solutions at concentrations of 11%, 16% and 20%, as well as 2% CHX, did not reveal CFU/mL of the S. aureus strain, indicating the broad spectrum of antibiofilm action of these disinfectant solutions. In addition, the Daro Brand® antimicrobial liquid agent showed lower CFU/mL in both maxillofacial elastomers compared to the Daro Brand® gel soap and 0.9% saline solution. Therefore, disinfection with PGL solutions is effective and might be considered to be a promising alternative in eliminating the S. aureus biofilm from specimens of maxillofacial elastomers by immersion for 15 minutes.